Estudo de dois grupos de alunos, submetidos a diferentes metodologias, quanto ao nível de informação e de desenvolvimento cognitivo - Goulart, Neide Macedo (1980)
The objective of the present work is to evaluate the mental development and information levels attained by two groups of students who were submitted to different methodologies, as well as to ascertain whether a significant difference exists between said groups. The research is divided into two stages. Of these, the first one regarded the main philosophical streams, some of the learning theories, and get's concept of the psychology of summarizes Jean Piaget mental. The second stage analyses a sample made up development. of students from two schools who are attending the 8th grade. For the mental development levels, there were used the tests from Piaget and from his followers. For information levels, language (Portuguese) and Sciences tests were employed. The results obtained evidenced that in the groups under study, be10nging to a privileged social class, mental deve10pment is independent of the methodology used. There was a marked difference, at the leve1 of 17, in the 1anguage (Portuguese) tests in favor of the traditional methodo1ofy. In the Sciences test both groups tied the score. It is suggested that further research be carried out, in order to supplement this work.